His-Purkinje conduction system pacing and atrioventricular node ablation in treatment of persistent atrial fibrillation refractory to multiple ablation procedures: A case report - Peng Qi; Hui An; Yuxuan Lv; Yanping Geng; Shuxia Chen; Shuren Li; Yi Dang (SAGE Open Medical Case Reports, 2023)
In patients with symptomatic atrial fibrillation refractory to optimal medical therapy, atrioventricular node ablation followed by permanent pacemaker implantation is an effective treatment option. A 66-year-old woman with symptomatic persistent atrial fibrillation refractory to multiple ablation procedures was referred to our institution. After optimal drug therapy, the patient still had obvious symptoms. Sequential His-Purkinje conduction system pacing and atrioventricular node ablation were performed. Left bundle branch pacing was used as a backup pacing method if thresholds of His bundle pacing were too high or loss of His bundle capture occurred in the follow-up. At the 6-month follow-up, the European Heart Rhythm Association classification for AF was improved, the score of the Atrial Fibrillation Effect on Quality of Life was enhanced, and the 6-Minute Walk Test was ameliorated. The present case was subjected to His-Purkinje conduction system pacing in combination with atrioventricular node ablation as treatment for a symptomatic persistent atrial fibrillation refractory to multiple ablation procedures, and this procedure alleviated symptoms and improved the quality of life in a short-term follow-up.